The Effect of SQ3R Method On Improving Students’ Reading Skill - Alvin Nabilla; Candra Hadi Asmara (Universitas Negeri Semarang, 2022)
The comprehension of reading texts and searching for information in texts requires methods in their implementation. One of the things that influences learning to read text is the information in the text and the student's reading method. Therefore, the most effective reading learning method is needed to be applied, and the learning method chosen is the SQ3R method. The purpose of this research is to see how the SQ3R approach influences students' understanding, knowledge, and interest in reading texts in class VIII SMP Muhammadiyah 4 Kebomas Gresik. The method used in this research is experimental research with a true-experimental design (pre- and post-test). The sample for this research is the class VIII students of SMP Muhammadiyah 4 Kebomas Gresik. Data collection used reading text information learning assessments and reading information tests to determine whether they correctly understood the content and information of the text they read. Non-test data collection using observation and photo documentation. The results of this study are that (1) the SQ3R learning method is effective in identifying reading text information for class VIII students of SMP Muhammadiyah 4 Kebomas Gresik, with an average increase of 61.90 to 78.81. This is evidenced by the sign value = 0.000 <0.05, which means that there is a significant difference in learning outcomes between the pretest and posttest experimental groups using the SQ3R learning method. Learning to read texts based on class VIII students of SMP Muhammadiyah 4 Kebomas Gresik using SQ3R is an effective learning method. This learning result has increased from an average of 61.90 to 78.81. This is evidenced by the sign value = 0.000 <0.05, which means there is a significant difference in student learning outcomes in the pretest posttest experimental group using the SQ3R learning method.